2000
DOI: 10.2175/106143000x137518
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Constructed Wetlands in Treating Urban Stormwater Runoff

Abstract: An investigation was conducted on the pollutant removal performance of a constructed wetlands treating stormwater runoff from a residential townhome complex in northern Virginia. Constituent event mean concentrations for 33 runoff events between April 1996 and May 1997 were measured based on flow‐weighted composite samples collected at the facility's inlet and outlet. With the results from a limited number of grab samples representing ungauged overland drainage from an adjacent wooded area, estimated removals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 8 publications
2
29
0
1
Order By: Relevance
“…Traditional urban stormwater management often utilized dry detention ponds and focused on peak flow attenuation while doing little to address nutrient impacts. More recently, wet retention ponds designed with permanent pools have been introduced in an effort to address stormwater quality along with quantity (Carleton et al, 2000;Hogan and Waldbridge, 2007). These stormwater ponds are ubiquitous in the American urban landscape with an estimated 2.6 million such ponds across the contiguous US (Smith et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditional urban stormwater management often utilized dry detention ponds and focused on peak flow attenuation while doing little to address nutrient impacts. More recently, wet retention ponds designed with permanent pools have been introduced in an effort to address stormwater quality along with quantity (Carleton et al, 2000;Hogan and Waldbridge, 2007). These stormwater ponds are ubiquitous in the American urban landscape with an estimated 2.6 million such ponds across the contiguous US (Smith et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Other BMPs have been investigated for urban stormwater treatment, including stormwater wetlands (Carleton et al, 2000;Kadlec and Wallace, 2009) and have performed effectively, but land availability is a common limitation. Traditional designs are often land intensive and not economically feasible in urban areas (Hunt and Wossink, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, these systems were designed for flood control: collecting, storing, and treating stormwater; also to minimize the effects on the infrastructure (such as soil impermeabilization and increase of water demand) and the anthropic activity on the quality of water [27]. The application of SUDS is a current topic (except in Africa); around the world there are successful SUDS experiences: USA [28], United Kindom [29], Chile [30], Malaysia [31], Australia [32], China [33], Korea [34], and Greece [35].…”
Section: Introductionmentioning
confidence: 99%
“…Constructed wetlands for the treatment of urban and agricultural stormwater are of recent interest due to their natural tendencies to filter and absorb nutrients and other contaminants from water. One study found decreased contaminant concentrations in the effluent from a constructed wetland, created by the simple installation of an outlet weir to an existing dry detention pond and the growth of natural volunteer wetland species (Carleton et al, 2000).…”
Section: Stormwater Treatmentmentioning
confidence: 99%